Design and fabrication of cleaning device for offices / Muhammad Irfan Zikri Zamzuri - Zamzuri, Muhammad Irfan Zikri (2022)
Cleaning is essential one to make the environment sanitary. Many cleaning devices for office are avaible in the market such as mop, vacuum, brush, and others. Nowadays, the current mop design has limited function ability where the human need to use extra energy to use the mop. The current mop also rotates 90%, thus the efficiency of cleaning process also cannot be achieved. In this project, new mop design will be fabricated that consist of multifunction, lightweight and easy to handle. Some manufacturing process will be use in this project such as milling, cutting, drilling etc. As a result, a lightweight with multifunctional mop that will help human being reduce to energy usage and at the same time save the time.